High D-dimer plasma concentration in systemic sclerosis patients: Prevalence and association with vascular complications. Issue 2 (June 2021) - Furtado, Sofia; Dunogué, Bertrand; Jourdi, Georges; Chaigne, Benjamin; Chibah, Aziza; Legendre, Paul; Mouthon, Luc
Objective: To determine the frequency of elevated D-dimer plasma concentration (>500 ng/mL) in patients with systemic sclerosis and evaluate its association with systemic sclerosis–specific microvascular and macrovascular complications. Methods: Retrospective observational study of patients with systemic sclerosis followed in a tertiary referral center with at least one measurement of D-dimer between 2010 and 2018. Results: A total of 214 patients were analyzed. Mean age at inclusion was 55.1 ± 14.7 years; 180 (84.1%) were female; 74 (34.6%) had diffuse cutaneous systemic sclerosis. Anti-Scl70 and anti-centromere antibodies were positive in 74 (34.6%) and 75 (35.0%) patients, respectively. D-dimer level was elevated in 93 (43.5%) patients, independently of cutaneous subtype (44.6% in diffuse cutaneous systemic sclerosis vs 42.9% in limited cutaneous systemic sclerosis, p = 0.81). At least one microvascular complication was found in 108 (50.5%) patients: 105 (49.1%) with previous or current digital ulcers, 6 (2.8%) with renal crisis, and 4 (1.9%) with pulmonary arterial hypertension. Microvascular complications were more frequent in patients with elevated D-dimer (57.0% vs 45.5%, p = 0.09), significantly so after exclusion of patients with a history of cancer and/or venous thromboembolism (60.5% vs 44.8%, p = 0.04). Macrovascular complications were detected in 15 (7.0%) patients and were associated with a high D-dimer level (11.8% vs 3.3%, p = 0.03). Over a median follow-up of 2.3 years [1.1–3.3] after D-dimer measurement, new macrovascular complications occurred only in patients with high D-dimer (n = 8). Conclusion: High D-dimer levels are frequently found in systemic sclerosis patients and seem to be associated with the occurrence of macrovascular and microvascular complications after adjustment for confounding factors.